Status of Science education and ICT at Secondary school stage in Aspirational Districts of North India: An Analysis of NAS 2021 District Report - Kumar, Dheeraj; Ali, Mohd Mamur (Indian Journal of Educational Technology, 2024)
This study aimed to examine the status of science education and ICT at the secondary school stage in the Aspirational Districts of North India. For this study, the districts report card of the National Achievement Survey (NAS) District Report 2021, which was considered a data source for 22 aspirational districts of six states and one Union Territory in North India. The secondary data were statistically analysed using frequencies, percentages, and averages. Finding of the study reveals that (1) students’ performance level decreases as they progress from the basic level to the advanced level, and not satisfactory (2) aspirational districts of North India show positive up to some extent developments in science education for girls, (3) the current state of science education indicates that students are not achieving the expected learning outcomes, and (4) the status of ICT is not in a good position in terms of accessibility to digital devices, particularly regarding internet connectivity and the adequacy of audio-visual resources in all aspirational districts of North India. Study concluded that the status of science education and ICT are not in good position in most of the aspirational districts of North India. Therefore, more collective efforts are needed to improve science education and ICT integration at the secondary school stage.